RANCANG BANGUN EARLY WARNING SYSTEM DAN MONITORING DVOR (DOPPLER VHF OMNIDIRECTIONAL RANGE) BERBASIS APLIKASI ANDROID - Fidya Aurio Nursafrudin; Moch Rifa'i; Romma Diana Puspita (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
DVOR is a navigation tool that is often used by an airport, because it is easy to maintain and easy to use. It is not only airports that use these navigation tools. The Surabaya Aviation Polytechnic has used DVOR and is used as a learning facility for cadets. DVOR that is used must have supervision from both the user and the serial computer, because there is no DVOR remote monitoring available, and only one monitoring is using a serial PC, the researcher wants to make a design that can be done remotely. The purpose of this design is to create a monitoring system for one of the navigation tools, namely the Doppler VHF Omnidirectional Range with the Intel NUC which can be accessed via a web server-based smartphone to make it easier for users to monitor the tool. Intel NUC is one of the tools that has a processor as a monitoring system. Remote monitoring of DVOR parameters and no need to enter the laboratory room, can be anywhere and anytime because DVOR monitoring can be done through the Android application.